Developing the value clarification technique of law (VCTL) model to strengthen digital citizenship in high school learning - Angraini, Rita; Sapriya, Sapriya; Rahmat, Rahmat; Masyitoh, Iim Siti; Habibah, Siti Maizul; Isnarmi, Isnarmi; Kurniawati, Eni (Association for Scientific Computing Electrical and Engineering(ASCEE), 2024)
This study aims to analyze and develop the Value Clarification Technique of Law (VCTL) learning model to strengthen high school students’ understanding of digital rights and responsibilities in Padang City. While students have the freedom to access internet technology, they are also expected to use it responsibly and respect the rights of others in digital spaces. The development of the VCTL model was motivated by the growing concern over students’ unwise behavior in using the internet, highlighting the need for an educational approach that fosters ethical awareness and value-based decision-making. This research adopts a Research and Development (RD) methodology using the ADDIE model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. The final product is a model book designed to assist teachers in implementing the VCTL approach in high school classrooms. The findings indicate that the VCTL model effectively enhances students’ digital responsibility by engaging them in structured value clarification processes anchored in legal and ethical considerations. The model encourages students to critically choose, clarify, and act upon values related to digital citizenship.